2017
DOI: 10.1186/s40621-017-0110-2
|View full text |Cite
|
Sign up to set email alerts
|

Select physical performance measures and driving outcomes in older adults

Abstract: BackgroundImproving physical functioning may be a future intervention to keep older adults driving safely longer as it can help maintain both physical and cognitive health longer. This systematic review assesses the evidence on the association between three physical functioning measures: the Short Physical Performance Battery, the Timed Up-and-Go test, and the Rapid Pace Walk with driving outcomes in older adults.MethodsOlder adult studies published between 1994 and 2015 that included the Short Physical Perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 70 publications
(138 reference statements)
0
14
0
1
Order By: Relevance
“…The results showed that older adults who had difficulty climbing stairs as an indicator of lower extremity function were 1.50 times more likely to stop driving. Changes in muscle strength and flexibility affect changes in muscle length of the lower extremity musculature [ 43 ] and lead to a decrease in lower extremity function, eventually increasing the DC rate [ 44 ]. Therefore, the assessment of physical function, such as lower extremity function, is required to determine the need for DC.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that older adults who had difficulty climbing stairs as an indicator of lower extremity function were 1.50 times more likely to stop driving. Changes in muscle strength and flexibility affect changes in muscle length of the lower extremity musculature [ 43 ] and lead to a decrease in lower extremity function, eventually increasing the DC rate [ 44 ]. Therefore, the assessment of physical function, such as lower extremity function, is required to determine the need for DC.…”
Section: Discussionmentioning
confidence: 99%
“…This aspect reinforces the relevance of identifying and proposing actions to elderly drivers with reduced GS. Improvement of physical functioning (GS and muscle strength) should be the focus of interventions for helping the elderly to maintain a safe driving ( 43 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Successful aging and physical function contribute to both driving safety and cognitive function [5]. Mielenz et al [8] reviewed 13 studies on physical function and driving outcomes, including driving ability, cessation, and car crashes. They suggested that the short physical performance battery score – a comprehensive tool for assessing physical function [9] – is useful to assess the risk of driving outcomes, while simple mobility tests such as the Timed Up and Go test are not useful [8].…”
Section: Introductionmentioning
confidence: 99%
“…Mielenz et al [8] reviewed 13 studies on physical function and driving outcomes, including driving ability, cessation, and car crashes. They suggested that the short physical performance battery score – a comprehensive tool for assessing physical function [9] – is useful to assess the risk of driving outcomes, while simple mobility tests such as the Timed Up and Go test are not useful [8]. The evaluation of frailty also covers comprehensively and commonly included physical functions such as the Cardiovascular Health Study index [10].…”
Section: Introductionmentioning
confidence: 99%